Supervised practicum in physical education in brazil: A scoping review of theses and dissertations - De Carvalho Filho, Josué José; Batista, Paula; De Souza Neto, Samuel [UNESP] (Universidade Federal do Rio Grande do Sul, 2021)
This Scoping Review mapped production of knowledge (PhD theses and Master’s dissertations) about supervised practicum in Physical Education teacher training in Brazil between 1996 and 2019, to identify relevant factors that contribute to professionalize teaching. Anchored in Arksey and O’Malley (2005) and in the “Prisma-ScR” guide (TRICCO et al., 2018), searches took place on the CAPES and BDTD online platforms, using the Portuguese descriptors for “Supervised Curricular Practicum”; “Curricular Practicum”; “Supervised Practicum”; “Teaching Practice”; “Supervised School Placement” AND “Teacher Training”, AND “Physical Education.” They found 62 papers (46 dissertations and 16 theses). The data reveal an increase in research between 2012-2019, greater concentration in the South/Southeast Brazil axis (83%) and scarcity in the North (3%), Northeast (11%) and Center-West (3%). The investigation highlighted the need to implement the university-school partnership in terms of formative roles of institutions and actors involved in practicum.
LA PRÁCTICA SUPERVISADA EN EDUCACIÓN FÍSICA EN BRASIL: UNA SCOPING REVIEW DE TESIS Y DISERTACIONES
O ESTÁGIO SUPERVISIONADO EM EDUCAÇÃO FÍSICA NO BRASIL: UMA SCOPING REVIEW DE TESES E DISSERTAÇÕES
Keywords: Physical Education; Professional Practice; Review; Teaching